2017
DOI: 10.1007/s10792-017-0598-z
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of cataract surgery in patients with anterior uveitis

Abstract: The long-term outcomes of phacoemulsification with intraocular lens implantation in patients with uveitic cataract were satisfactory with excellent visual acuity and relatively low complication rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
16
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 31 publications
5
16
1
Order By: Relevance
“…The nal BCVA of 0.5 or higher was achieved in 71.5% of eyes which is comparable to previously reported data, where the nal BCVA ranged from 47-87.3% [2-4, 9, 10, 12, 14, 16]. The highest percentage of eyes achieving BCVA 0.5 or better was seen in anterior uveitis, which is in line with previous reports [2,4,9,10,14,16]. However, 65.3% of patients with intermediate uveitis achieved BCVA 0.5 or better, which is better than previously reported.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The nal BCVA of 0.5 or higher was achieved in 71.5% of eyes which is comparable to previously reported data, where the nal BCVA ranged from 47-87.3% [2-4, 9, 10, 12, 14, 16]. The highest percentage of eyes achieving BCVA 0.5 or better was seen in anterior uveitis, which is in line with previous reports [2,4,9,10,14,16]. However, 65.3% of patients with intermediate uveitis achieved BCVA 0.5 or better, which is better than previously reported.…”
Section: Discussionsupporting
confidence: 91%
“…It develops due to a combination of prolonged in ammation and treatment with corticosteroids and affects 50-70% of patients [1][2][3]. As opposed to age-related cataracts, patients with uveitis tend to be younger, often exhibiting co-pathology such as cystoid macular edema (CME) and elevated intraocular pressure (IOP) [4][5][6][7][8]. Furthermore, the surgery is more challenging due to miotic pupil, posterior synechiae, iris atrophy, zonular weakness, and pupillary membrane [1,4,9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The risk is even higher in uveitic eyes[ 87 90 97 ] especially in younger patients. [ 49 98 ] The incidence of PCO in uveitic eyes is 34.2-81.7%[ 96 97 99 ] and 3.6-32.2% require Nd:YAG capsulotomy. [ 96 97 99 ] Nd:YAG capsulotomy is indicated when the visual acuity is reduced or when visibility of the posterior segment is compromised due to PCO.…”
Section: Postoperative Complicationsmentioning
confidence: 99%
“…In fact, few studies have looked at IOP outcomes in eyes with uveitis undergoing cataract surgery. Balta et al found that 9 of 55 eyes with uveitis that underwent cataract surgery had elevated IOP [ 16 ]. Mora et al studied 52 eyes, and although average 2-week postoperative IOP was elevated, IOP at final follow-up was not significantly different than baseline [ 17 ].…”
Section: Discussionmentioning
confidence: 99%